The Sources behind “The Gifts and the Calling of God Are Irrevocable” (Rom 11:29): A Reflection on Theological Questions Pertaining to Catholic-Jewish Relations on the Occasion of the 50th Anniversary of Nostra Aetate (No. 4) - Cunningham, Philip A. (Studies in Christian-Jewish Relations, 2017)
The 2015 Vatican statement, "The Gifts and the Calling of God Are Irrevocable" frequently draws upon or alludes to phrases and formulations found in earlier texts from Catholic ecclesiastical offices and officials without always directly citing them. By means of extensive footnotes, this version of "Gifts and Calling" provides the original wordings behind many of these allusions and references.